1998
DOI: 10.1095/biolreprod59.3.643
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Stimulates Proliferation but Not Migration or Invasiveness in Human Extravillous Trophoblast1

Abstract: Vascular endothelial growth factor (VEGF) is a homodimeric glycoprotein that promotes angiogenesis and vascular hyperpermeability and interacts with two receptors, fms-like tyrosine kinase (Flt-1) and kinase domain-containing region (KDR). In situ localization in the pregnant human uterus revealed that VEGF mRNA is expressed primarily by the maternal decidua, whereas the receptor Flt-1 is expressed primarily by chorionic vascular endothelium and trophoblast cells-in particular, the extravillous trophoblast (EV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(42 citation statements)
references
References 36 publications
4
34
0
3
Order By: Relevance
“…It has been shown that reduced serum levels of the angiogenic factor placental growth factor (PlGF), which is an important factor in the proliferative nature of trophoblast cells, is better at predicting the development of PE in obese pregnant women compared with underweight/lean counterparts when assessed early in the second trimester (5,56). This corroborates observations that obese women have reduced fetoplacental vascularity characterized by villi having large diameters and low numbers of capillaries (42).…”
Section: Effects Of Obesity On the Placental Function And Perfusionsupporting
confidence: 53%
“…It has been shown that reduced serum levels of the angiogenic factor placental growth factor (PlGF), which is an important factor in the proliferative nature of trophoblast cells, is better at predicting the development of PE in obese pregnant women compared with underweight/lean counterparts when assessed early in the second trimester (5,56). This corroborates observations that obese women have reduced fetoplacental vascularity characterized by villi having large diameters and low numbers of capillaries (42).…”
Section: Effects Of Obesity On the Placental Function And Perfusionsupporting
confidence: 53%
“…Evidence in support of this is the presence of an increased mRNA expression for both membrane and soluble forms of VEGFR-1 in syncytiotrophoblasts of hypoxic/ischemic villi of preeclamptic patients [75]. Alternatively, since VEGFR-1 and its ligands (VEGF and PlGF) are involved in angiogenesis and trophoblast proliferation/differentiation [37,38,40,[76][77][78][79][80][81][82], it is possible that the increased expression of VEGFR-1 in trophoblasts may relate to the remodeling process of the villous tree in response to chronic uteroplacental insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain the morphological changes observed in IUGR, high altitude pregnancy and maternal anemia [43]. In vitro, VEGF121 and PlGF1 without heparin-binding domains, promote proliferation of CT cell lines but have no effect on their migration [6,7]. Heparan sulfate may modulate the activity of some VEGF isoforms and of PlGF2.…”
Section: Villous and Vascular Changes In Pathological Pregnanciesmentioning
confidence: 99%